Penyelesaian Sengketa Perbankan Syariah oleh Pengadilan Agama Kota Batam Pasca Putusan Mahkamah Konstitusi Nomor 93/PUU-X/2012 - Agus Riyanto; Rizki Tri Anugrah Bhakti (Faculty of Law Hang Tuah University, 2018)
Islamic banking is experiencing growth both in Indonesia and in the world. In Indonesia, the growth of the number of Islamic bank offices continued to grow. This shows that community needs for Islamic banks are very high. The government of course has to deal with this development. The most substantial improvement is the existence of policies regarding the regulation of Islamic banking. This is very important because the banking sector is very sensitive, especially the possibility of a dispute between the customer and the bank is also quite large. These disputes must eventually be resolved by both parties, namely the bank and the customer because both of these parties have the same position as the parties concerned. This study aims to describe the competence of the Religious Courts in resolving sharia banking disputes as well as knowing the obstacles faced by the Religious Courts in deciding Islamic banking disputes. The type of research used is empirical juridical. The results of the study can be a reference for further research and become a reference source for related subjects.